Selective modulation of cellular voltage-dependent calcium channels by hyperbaric pressure—a suggested HPNS partial mechanism - Aviner, Ben; Gradwohl, Gideon; Mor Aviner, Merav; Levy, Shiri; Grossman, Yoram (Frontiers in Cellular Neuroscience, 2014)
Professional deep sea divers experience motor and cognitive impairment, known as High Pressure Neurological Syndrome (HPNS), when exposed to pressures of 100 msw (1.1MPa) and above, considered to be the result of synaptic transmission alteration. Previous studies have indicated modulation of presynaptic Ca2+ currents at high pressure. We directly measured for the first time pressure effects on the currents of voltage dependent Ca2+ channels (VDCCs) expressed in Xenopus oocytes. Pressure selectivity augmented the current in CaV1.2 and depressed it in CaV3.2 channels. Pressure application also affected the channels' kinetics, such as ƮRise, ƮDecay. Pressure modulation of VDCCs seems to play an important role in generation of HPNS signs and symptoms.